Spiro Metric and Some Sellctive Immunological Changes Among 49 Cases of Different Respiratory Diseases (Journal of Chittagong Medical College Teachers' Association, 2012)
Total 49 patients having different types of respiratory diseases were selected to evaluate their Spiro metric and IgG, IGE related blood changes. Out of these 49 respondents, 27 were females and 22 were males. 9 patients were more than 60+ years of age. Among the sufferers, 10 had bronchial asthma, 22 patients had bronchitis. Illness duration varied from 30 years; 14 male respondents had smoking habit. 50% of the respondents had hereditary trend of present respiratory disease, 5 cases had drug addiction. Chest X-ray was performed for 48 cases, abnormality revealed in 13 cases. Out of40 routing examination of blood, 13 had eosonophilia and raised ESR values. 15 respondents had eosonophil count 10-15%, 4 had >20%. Spirometry performed on 28 respondents. 07(25%) of the cases revealed abnormal feature-out of these, 02(29%) were obstructive and 5(71%) were restrictive1. Mean FVC and FEV1 of the restrictive cases were 59.42% and 52.68% respectively. Both are